Effect of Saccharomyces boulardii supplementation to bismuth quadruple therapy on Helicobacter pylori eradication - Yi-Zhou Jiang; Kai Ma; Cheng Cui; Zhuo-Ya Li; Xiao-Yong Wang (BMC Gastroenterology)
Abstract Background Helicobacter pylori (H. pylori) infection is a common chronic infection, and there are over half of the global population infected with H. pylori. It is still controversial whether the supplementation of Saccharomyces boulardii (S. boulardii) to bismuth quadruple therapy is beneficial for H. pylori eradication. Aim To determine the effects of S. boulardii supplementation to bismuth quadruple therapy on H. pylori eradication. Methods We performed a systematic literature search across PubMed, Embase, Web of Science, and China National Knowledge Infrastructure for articles published up to October 2023. We calculated the pooled relative risk (RR) with the 95% confidence interval (CI). Statistical analyses were conducted using Stata/SE 15.1 software. Results Ten randomized controlled trials were included. Notably, S. boulardii supplementation to bismuth quadruple therapy significantly improved H. pylori eradication rates (RR = 1.08, 95% CI: 1.04–1.12) and reduced the incidence of total adverse effects (RR = 0.53, 95% CI: 0.45–0.62). Specifically, it reduced the incidence of some gastrointestinal adverse effects and nonspecific adverse effects, including diarrhea (RR = 0.28, 95% CI: 0.22–0.36), constipation (RR = 0.32, 95% CI: 0.18–0.55), abdominal distention (RR = 0.39, 95% CI: 0.26–0.59), nausea (RR = 0.59, 95% CI: 0.36–0.97), and rash (RR = 0.49, 95% CI: 0.28–0.86). In the subgroup analysis, long-term eradication duration (> 10 days; RR = 1.08, 95% CI: 1.04–1.13) and S. boulardii supplementation to be started and stopped at the same time as eradication treatment (RR = 1.09, 95% CI: 1.04–1.14) were found to significantly improve the eradication rate regardless of the S. boulardii dose (500 mg/day, RR = 1.10, 95% CI: 1.03–1.17; 1000 mg/day, RR = 1.08, 95% CI: 1.03–1.12). Conclusions The addition of S. boulardii to bismuth quadruple therapy significantly increased H. pylori eradication rates and decreased the adverse effects. We recommend adding 500 mg/day S. boulardii concurrently with bismuth quadruple therapy and continuing this therapy for > 10 days for optimal H. pylori eradication efficacy.